Modelling the Effects of Radioactive Effluent on Thunnus orientalis and Oncorhynchus gorbuscha - Zhixiong Chen; Yi Ding; Rusty Laracuenti; Bernard Lipat (Journal of Applied Mathematics)
The contamination of the Pacific Ocean by the radioactive pollutants released from the Fukushima Daiichi Nuclear Power Plant has raised legitimate concerns over the viability of marine wildlife. We develop a modified Crank-Nicholson method to approximate a solution to the diffusion-advection-decay equation in time and three spatial dimensions to explore the extent of the effects of the radioactive effluent on two marine species: the Pacific Bluefin Tuna (Thunnus orientalis) and the Pacific Pink Salmon (Oncorhynchus gorbuscha).